Mobile language app learners’ self-efficacy increases after using generative AI - Kittredge, Audrey K.; Hopman, Elise W. M.; Reuveni, Ben; Dionne, Danielle; Freeman, Cassie; Jiang, Xiangying (Frontiers in Education, 2025)
IntroductionAlthough generative artificial intelligence (AI) is ubiquitous, there is little research on how it supports self-efficacy (learners’ belief that they can perform at a particular level on a specific task). The purpose of these studies was to investigate self-efficacy development in a generative AI-based language learning experience.MethodsIn two studies, learners (N = 385) of French/Spanish used AI-based features offering conversation practice and on-demand explanations in a mobile app (Duolingo) for 1 month. Before and after using the features, learners reported their self-efficacy and other perceptions.ResultsIn Study 1, learners who had already used the features felt significantly more prepared to use French/Spanish in real-life situations after 1 month, as did learners in Study 2 who used the features for the first time. Learners in Study 2 also felt significantly more prepared to share their opinions and navigate a city, and reported significantly higher self-efficacy for speaking and understanding grammar and mistakes. Across studies, the majority of learners agreed that the AI-based features effectively supported learning, and reported using their learning outside the app.DiscussionThese results provide the first evidence of enhanced language learning self-efficacy after use of generative AI, building on findings from classroom interventions.